Effective Combination Therapy of Polymyxin‐B Direct Hemoperfusion and Recombinant Thrombomodulin for Septic Shock Accompanied by Disseminated Intravascular Coagulation: A Historical Controlled Trial. Issue 5 (7th October 2013) - Yamato, Masafumi; Minematsu, Yusuke; Fujii, Junya; Mori, Kohei; Minato, Takumi; Miyagawa, Sachie; Fujimura, Ryuta; Morikage, Naoko; Arata, Yuka; Nakano, Chisako; Wada, Akira; Ito, Takahito
Abstract Disseminated intravascular coagulation (DIC) and multiple organ failure often occur via the crosstalk between inflammation and coagulation, which is mediated by High Mobility Group Box 1 (HMGB1). In septic shock, Polymyxin‐B direct hemoperfusion (PMX‐DHP) ameliorates hemodynamics by endogenous cannabinoid adsorption and improves pulmonary oxygenation by indirect cytokine reduction through the adsorption of activated mononuclear cells. However, PMX‐DHP has no direct effect on HMGB1 circulating in the plasma. In cases with DIC, recombinant thrombomodulin (rTM), an effective drug for DIC, exerts not only anticoagulation but also antiinflammatory properties via direct anti‐HMGB1 activity. Therefore, a combination of PMX‐DHP and rTM is expected to block the vicious cycle of a cytokine storm ending up with multiple organ failure in DIC. The aim of this study was to investigate the efficacy of combination therapy for septic shock associated with DIC. This study comprised 22 consecutive patients with sepsis‐induced DIC who received PMX‐DHP. The initial eight patients were treated without rTM (historical control group), and the following 14 patients were given rTM (rTM group). The baseline Sequential Organ Failure Assessment (SOFA) score or age was not different between both groups. Sixty‐day survival rate in the rTM group was significantly higher than that in the control group (85.7% vs. 37.5%, P = 0.015). A combination of PMX‐DHP and rTM may be effective in septic shock accompanied by DIC and is expected to improve survival rates.